Constructing practice-oriented futures for sustainable urban food policy in Bangkok. (May 2022) - Kantamaturapoj, Kanang; McGreevy, Steven R.; Thongplew, Natapol; Akitsu, Motoki; Vervoort, Joost; Mangnus, Astrid; Ota, Kazuhiko; Rupprecht, Christoph D.D.; Tamura, Norie; Spiegelberg, Maximillian; Kobayashi, Mai; Pongkijvorasin, Sittidaj; et al.
Abstract: Conventional policy approaches emphasize technical solutions and individual behavioral change, but practice-based policy approaches offer an alternative. This paper examines the operationalization of a practice-oriented futures policy development process. The process builds on practice theory to generate alternative sustainable future pathways and policy intervention ideas, and in doing so, extends the vocabulary for policy-focused futures work. We focus on three practices with implications for urban sustainability - food purchasing, eating out, and home cooking in Bangkok, Thailand. A multi-phase process of interlinked workshops including visioning, scenario evaluation, and transition pathways was enacted with food system actors and policy makers. Role-play and narrative elements were incorporated to elicit transformative and systems knowledge on how practices are or might be embedded in everyday life and generated policy ideas to enable such practices to emerge in the future. Different practices showed varying degrees of amenability to the process, based on participants' sense of agency and individual and community-based practice memories. This paper contributes to our understanding of how future practices are co-constructed and how policies might guide practice trajectories in the future. Practice-oriented futures policy development opens pathways for integrated policy ideas, mirroring the growing recognition for integrated governance structures. Highlights: Urban food policy ideas were developed through a practice-oriented futures process. Future practices are co-constructed and policies guide practice trajectories. Practice-based policy approaches will benefit from integrated governance.